Computational thermodynamic study of SiC chemical vapor deposition from MTS‐H2. Issue 7 (19th March 2021) - Peng, Jian; Jolly, Brian; Mitchell, David J.; Haynes, J. Allen; Shin, Dongwon
Abstract: This study focuses on the computational thermodynamic analysis of the chemical vapor deposition (CVD) of SiC from the methyltrichlorosilane‐hydrogen (MTS‐H2 ) using up‐to‐date thermodynamic databases. High‐resolution computation has been performed with the fine intervals of temperature and pressure at the various H2 /MTS ratios of interest to systematically investigate the deposition condition range (800 to 1600°C, 0 to 26 664 Pa, and H2 /MTS ratios of 0.1 to 100) to guide experimental exploration. The influence of deposition parameters on the compositions and phase stabilities of the deposit and gas phase pertinent to vapor processing is elucidated. Low pressure and medium temperatures (1000 to 1400°C) are beneficial to reaching a higher SiC deposition efficiency and provide an optimal window for preparing a high‐purity (>99 wt.% SiC) deposit. This optimal processing window expands significantly with an increasing H2 /MTS ratio (<20). These results are supported by a number of previous theoretical and experimental observations. The mass fraction of SiC in deposit is proposed as an additional perspective to understand the discrepancy between thermodynamic calculation and experimental observation of pure CVD SiC at low H2 /MTS ratios.